Evaluation of time to aneurysm treatment following subarachnoid hemorrhage: comparison of patients treated with clipping versus coiling. (12th March 2015) - Attenello, Frank J; Reid, Patrick; Wen, Timothy; Cen, Steven; Kim-Tenser, May; Sanossian, Nerses; Russin, Jonathan; Amar, Arun; Giannotta, Steven; Mack, William J; Tenser, Matthew
Abstract : Introduction: Prior studies of aneurysmal subarachnoid hemorrhage (SAH) have shown that treatment at teaching institutions and decreased time to surgery are factors that correlate with improved patient outcome. We aimed to individually evaluate the effect of teaching institution treatment on rates of surgical clipping or endovascular coiling. Methods: Patients with SAH treated by either aneurysm clipping or coiling between 2002 and 2010 in the Nationwide Inpatient Sample were analyzed. Time to aneurysm treatment was dichotomized to >3 days or ≤3 days and evaluated by multivariable logistic regression modeling, controlling for patient and hospital covariates. Identified predictors for prolonged time to procedure were compared between the clipping and coiling populations. Results: Between 2002 and 2010 there were 90 684 SAH admissions with subsequent clipping and coiling procedures. Treatment at teaching hospitals was associated with faster time to clipping (OR 0.60, 95% CI 0.44 to 0.80, p=0.001) but not coiling procedures (p=0.66). Likewise, older age (≥80 years) was associated with delays to clipping (p<0.05) but not coiling procedures (p>0.05). Patients with delayed time to treatment were associated with increased rates of moderate to severe neurological disability. Conclusions: Older patients with SAH and those treated at non-teaching hospitals were more likely to have delays to aneurysm clipping procedures. These associations were unique to open surgery as age and hospital teaching status did not affect time to coiling procedures.